2015
DOI: 10.1186/s40199-014-0075-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of MY-DRG casemix pharmacy service weights in UKM Medical Centre in Malaysia

Abstract: BackgroundThe service weight is among several issues and challenges in the implementation of case-mix in developing countries, including Malaysia. The aim of this study is to develop the Malaysian Diagnosis Related Group (MY-DRG) case-mix pharmacy service weight in University Kebangsaan Malaysia-Medical Center (UKMMC) by identifying the actual cost of pharmacy services by MY-DRG groups in the hospital.MethodsAll patients admitted to UKMMC in 2011 were recruited in this study. Combination of Step-down and Botto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 19 publications
0
29
0
1
Order By: Relevance
“…Bottom-up costing records every item of service that a patient receives, and changes them into costs. Bottom-up costing gives more accurate results, but it requires a large investment of time and resources (Jadoo et al, 2015). Time-driven activity-based costing (TDABC) by Kaplan and Porter (2011) gives accurate cost information but it requires a lot of detailed data, e.g., time spent by doctors with patient and time spent by administration staff to serve patients.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Bottom-up costing records every item of service that a patient receives, and changes them into costs. Bottom-up costing gives more accurate results, but it requires a large investment of time and resources (Jadoo et al, 2015). Time-driven activity-based costing (TDABC) by Kaplan and Porter (2011) gives accurate cost information but it requires a lot of detailed data, e.g., time spent by doctors with patient and time spent by administration staff to serve patients.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…For instance, the output of a study on cost weights for treatment of cardiology showed that the range of cost weights was between 0.4710 and 0.7961, while the cost weights for orthopaedic cases were between 0.7438 and 1.8182 [25]. A study done by Ali Jadoo et al to determine the service weights for pharmacy showed that the range of pharmacy service weights was between 3.78 and 11.80 [26]. In a recent study by Roszita on the laboratory and radiology service weights, the laboratory service weights was between 1.6896 and 5.9609, while radiology service weights was between 1.6336 and 2.8461 [27].…”
Section: Introductionmentioning
confidence: 99%
“…1 The need for cost and pharmacoeconomics evaluations is well acknowledged. [2][3][4][5][6] In terms of health-policy comparatives and analytic techniques, health economic studies provide important and valuable information that enables health care decision makers to adjust and effectively use of pharmaceuticals. 3 In this article, we used normal linear specifications to test a number of factors (eg, sociodemographic, diagnostic, and drug data) that are thought to impact the total inpatient pharmacy cost (TINPC), and we compared our results with others from literature.…”
Section: Introductionmentioning
confidence: 99%
“…IPD captures the details of specific patient (depending on the data source) and serves as a potential tool to analyze pharmaceutical cost. 4 However, many countries including Malaysia are hindered by the lack of the availability of detailed illness costs at IPD, which can reflect negatively on 755483I NQXXX10.1177/0046958018755483INQUIRY: The Journal of Health Care Organization, Provision, and FinancingAljunid and Ali Jadoo research-article2018 1 Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia 2 Faculty of Public Health, Kuwait University, Kuwait the health economic analysis relevant to the local health care system. The National University of Malaysia Medical Center (UKMMC) was a pioneer that adopted and developed its own casemix and Malaysian Diagnosis-Related Groups (MY-DRGs) system in 2002.…”
Section: Introductionmentioning
confidence: 99%